Tabelas de esperança de vida e fertilidade para Lipaphis erysimi (Kalt.) (Hemiptera: Aphididae) em condições de laboratório e campo - Godoy, Karlla B. [UNESP]; Cividanes, Francisco J. [UNESP] (Springer Nature, 2002)
In this study, the aphid Lipaphis erysimi (Kalt) was reared at different temperatures, under laboratory and field conditions, aiming to obtain age-specific life tables. In the laboratory, L. erysimi was fed on kale, Brassica oleracea L. var acephala, and kept in incubators adjusted to 10, 15, 20, 25 and 30°C, 14h photophase and 70±10% RH. The longest mean generation time (T) was observed at 15°C (23.86 days) and the shortest at 30°C (7.18 days), while the smallest net reproductive rate (R0) occurred at 15°C (4.30) and largest one at 25°C (38.29). For the temperatures of 15, 20, 25 and 30°C, the intrinsic rate of natural increase (rm) and the finite rate of increase (λ) were 0.06/1.06, 0.24/1.27, 0.28/1.33 and 0.23/1.25, respectively. The doubling time (DT) at 15, 20, 25 and 30°C were 11.55, 2.80, 2.47, and 3.01 days, respectively. Under field conditions, the net reproductive rate (R0) of L. erysimi was larger in the winter (53.50) than in the summer (40.99), the same being observed for the mean generation time (T), which was 13.85 days in the winter and 7.57 days in the summer. The intrinsic rate of natural increase (rm) and the finite rate of increase (λ) were 0.29/1.34 and 0.40/1.63 for winter and summer, respectively. The doubling time (DT) observed for winter (2.39 days) was larger than the one observed for summer (1.41 days). The temperature affects longevity of L. erysimi and the best parameters of life table of fertility under laboratory conditions are obtained at 25°C. The data obtained in field conditions reinforced this finding. The daily fecundity was higher and longevity was smaller in the summer than in the winter, thus increasing the innate capacity of increasing in number and duplicating the population in a shorter period of time.
Age-specific life tables of Lipaphis erysimi (Kalt.) (Hemiptera: Aphididae) under laboratory and field conditions
Keywords: Aphid; Brassica oleracea; Insecta; Temperature